(untitled) (Journal of the Management Sciences, 2024)
The study x-rayed entrepreneurial skill acquisition as a veritable tool for sustainable national development. The study explained entrepreneurial skill acquisition as a concept, sustainable national development, benefits of entrepreneurial skill acquisition, challenges and ways forward. There are many entrepreneurial skills needed by the undergraduate and the youths which will lead to success in job creation, meaningful education for the youths, provide graduates with enough training and also reduce the high rate of poverty, insecurity and violence. It was revealed in the course of the study that entrepreneurial skills like innovativeness, creativity, communication, administrative and others were identified to be needed by youths for self-employability. It recommended among others that prospective entrepreneurs should ensure that necessary skills aimed at enhancing their businesses are acquired before venturing into their choice businesses; there should be a thorough knowledge of the pros and cons of businesses by prospective entrepreneurs before committing their financial resources and time to the business in order to avoid business failure and government at all levels should endeavour to promote small scale businesses by setting policies aimed at providing soft loans to intending investors in order to enhance speedy economic growth and development.